2014
DOI: 10.3233/rnn-139003
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain: The role of learning and brain plasticity

Abstract: Based on theoretical considerations and recent observations, we argue that continued suffering of chronic pain is critically dependent on the state of motivational and emotional mesolimbic-prefrontal circuitry of the brain. The plastic changes that occur within this circuitry in relation to nociceptive inputs dictate the transition to chronic pain, rendering the pain less somatic and more affective in nature. This theoretical construct is a strong departure from the traditional scientific view of pain, which h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
127
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(136 citation statements)
references
References 57 publications
4
127
0
5
Order By: Relevance
“…arthritis, low back pain) are under investigation [33, 34]. Moreover, key changes in brain volume, functional connections, and processing are observed using imaging studies [35, 36]. In patients with chronic back pain, studies have reported diminished cortical grey matter and impaired emotional decision making [37, 38].…”
Section: Overview Of the Pain Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…arthritis, low back pain) are under investigation [33, 34]. Moreover, key changes in brain volume, functional connections, and processing are observed using imaging studies [35, 36]. In patients with chronic back pain, studies have reported diminished cortical grey matter and impaired emotional decision making [37, 38].…”
Section: Overview Of the Pain Pathwaymentioning
confidence: 99%
“…In patients with chronic back pain, studies have reported diminished cortical grey matter and impaired emotional decision making [37, 38]. This observation has been expanded to other chronic pain states including chronic osteoarthritis pain [35, 36]. …”
Section: Overview Of the Pain Pathwaymentioning
confidence: 99%
“…Several studies suggested brain neuroplasticity is underlying to comorbidity of CP (Apkarian et al, 21 2009;Doan et al, 2015;Mansour et al, 2014) and the nucleus accumbens (NAc) has been 22 investigated as having a critical role in modulating CP in humans and animal models (Benarroch, 23 2016;Martikainen et al, 2015;Ren et al, 2015;Schwartz et al, 2017). 24…”
Section: Introductionmentioning
confidence: 99%
“…As a whole, these conditions concur to generate stereotyped network configurations, which seemingly appear as anatomo-functional counterparts of the continuous percept of pain, a picture recoverable from all the examined CP models. The model is theoretically sustained by the fact that persistent acute pain elicits massive hyperactivation of thalamocortical neurons strongly modifying the synaptic loads (Vierck et al 2013;Mansour et al 2014), which in turn dramatically alter the functional organization of the involved neuronal networks (Spisák et al 2017;Gustin et al 2012). In this dramatic context, actual conventional CP therapies do not appear adapt to relocate or repair within original limits the disordered network connectivity.…”
Section: Introductionmentioning
confidence: 99%